Analisis Semiotika pada Kumpulan Lagu Karya Mahalini Raharja - Rizki, Dhea Cahyanti (UIR PRESS, 2022)
This study examines the semiotics of Ferdinand de Saussure, namely the signifier and the signified in a collection of songs by Mahalini Raharja. Many researches on the semiotics of Ferdinand de Saussure in song lyrics have been carried out. However, in a collection of songs by Mahalini Raharja with the titles of the songs Perfect Story, Rest of Taste, Against Restu, and Bring Him Back, it has never been studied from the semiotic aspect of Ferdinand de Saussure. The problem examined in this study is: how is Ferdinand de Saussure's semiotics, namely the signifier and signified in a collection of songs by Mahalini Raharja? The purpose of this study is to describe, analyze, and interpret Ferdinand de Saussure's semiotics, namely the markers and signifiers in a collection of songs by Mahalini Raharya. The approach used is qualitative with content analysis method. Data collection techniques are non-participant observation techniques and literature study. In this study, the researcher made an interpretation by dividing the lyrics of a song by Mahalini Raharja into several lines and then the data included would be analyzed using Ferdinand de Saussure's semiotic theory. The results of the research and the amount of data on Ferdinand de Saussure's semiotics in the collection of Mahalini Raharja's songs amounted to 28 data.